Towards National Identity: Analysis of Children of Purus and Anticipation to Mentawai Future - Azmi Fitrisia; Wannofri Samry (Lembaga Penelitian dan Pengabdian Universitas Andalas, 2022)
This article aims to know some problems of children of Purus, a coastal area in Padang city, especially related to factors leading to literary poor imagination of ‘Kelompok Purus Menulis’ members. The experience in manage of children Purus could became guidelines to develop the future of Mentawai's children. They have attended training and mentoring programs in three years organized by Universitas Negeri Padang. But their quality product likes poem is still poor. They tend to imitate others’ works. Few are confident and stand out of box. Why? Data for this article are based on district document, and interview during the training and mentoring activities. After collecting the data, the analysis and written report for the result of research will follow. The analysis will show the poor imagination of Purus children. There are three reasons for that. First, the writer will have an extensive knowledge from reading, observing, and discussing with others. But Purus children rarely read and write. Second, family supporting. Some children of the community come from poor family background and lower level of education that hinder them from growing any better. Third, social environment. The children live in market and tourist area. It makes the children less focus on study.